Review of the Effectiveness of the Existing Municipal Solid Waste Management Systems in Uganda. Case Study of Kabale Municipal Council, Kabale Municipality, Kabale District. - Ainebyona, Joseph (Kabale University, 2023)
Municipal solid waste management Is the collection, transfer and disposal of the non-liquid and non-gaseous solid materials from residential, commercial, institutional, construction and demolishing and street sweeping within the urban centers of the country. It is a consequence of the day to day activities of the human kinds that need to be properly managed. This study was carried out to assess the effectiveness of the existing solid waste management systems in Uganda; a case study of Kabale Municipality, Kabale district. The study was guided by three specific objectives by observing and analyzing the solid waste characteristics, generation rate, collection, transportation, disposal and stakeholder roles and solid waste management responsibilities. A case study of this project was used in which a total of 57 respondents informed this study. These were reached through purposive and random sampling. Observation, questionnaires and interviews were used during the collection of data which was then analyzed both quantitatively and qualitatively. The study was adopted a combination of the above qualitative and quantitative designs to get a deeper understanding of the underlying issues with the municipal solid management practices in different settlements of the Municipality. Participants were selected purposively due to their essential knowledge and randomly to estimate the amount of solid waste generated in the area. However, the study scope was limited to households and commercial enterprises. According to the findings of the study, Kabale Municipal council uses different methods in the collection of solid waste, transporting it and later dispose it to a recognized site. The study found out that there is a big problem of sorting the solid waste depending on their characteristics, and that the council is under capacity to handle the solid waste as the existing systems are inefficient as large amount of waste is left uncollected and some just dumped on the verges of the streets. Where systems are poor or non-existent the community have developed onsite solid waste management systems such as waste recovery, recycling, re-use, incineration or burning and composting. As an intervention to solve the problems of persisted problems of inadequate solid waste management systems, an integrated solid waste management system was designed per each municipal division to employ the standard approaches of solid waste management, that is; rickshaw van collection system to effect solid waste collection, sorting, composting and a landfill for disposal of non-organic and inert solid waste material. The study concludes that the management and collection of the solid waste should not be a duty of either one person or organization, but rather all individuals. Therefore, there is need for KMC to include all the people in working for the clean and health threat-free environment. The study also suggest that KMC should try to effect the existing systems plus adopting the modern techniques for the collection, transportation and disposing of solid waste in Kabale Municipality.